Extraktion von Fichtenlignin mit einem stark eutektischen Lösungsmittel in Abhängigkeit der Partikelgröße. Issue 4 (16th February 2018) - Schäfer, Tobias; Eisenlauer, Moritz; Teipel, Ulrich
Abstract: As a consequence of the rising use of renewable raw materials, new raw material flows have to be developed and the process steps in the utilization of these have to be increased in their efficiency. Lignin is a potential source of mononuclear aromatic compounds. It is shown in this study that a eutectic mixture of choline chloride and 3‐phenyl propionic acid can serve as a potential extraction medium for lignin. To determine the yield, lignin was stained with phloroglucinol and quantified by UV/Vis spectroscopy. The yield was examined as a function of the particle size of spruce wood of a well‐defined source which was commuted under optimum conditions.